2013
DOI: 10.1088/0963-0252/22/1/015025
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of transient energy distributions in sub-ns streamer formation

Abstract: Abstract. Breakdown and streamer formation is simulated in atmospheric pressure nitrogen for a 2-D planar electrode system. A PIC code with multigrid potential solver is used to simulate the evolution of the non-equilibrium ionization front on sub-nanosecond timescales. The ion and electron energy distributions are computed, accounting for including inelastic scattering of electrons, and collisionally excited metastable production and ionization.Of particular interest is the increased production of metastable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Paxton et al (1986) suggest that 70% of the total energy input into a channel is optical radiation from the channel. MacLachlan et al (2013) demonstrate that the energy transfer calculation in a discharge channel needs to take into account a whole variety of collisional processes as for example elastic and inelastic scattering, metastable excitation, ionisation, metastable ionisation, electron-ion recombination. Hence, the precise value in Eq.…”
Section: Segment Lengthmentioning
confidence: 99%
“…Paxton et al (1986) suggest that 70% of the total energy input into a channel is optical radiation from the channel. MacLachlan et al (2013) demonstrate that the energy transfer calculation in a discharge channel needs to take into account a whole variety of collisional processes as for example elastic and inelastic scattering, metastable excitation, ionisation, metastable ionisation, electron-ion recombination. Hence, the precise value in Eq.…”
Section: Segment Lengthmentioning
confidence: 99%
“…The resulting self-electric field (i.e. the self-repulsion of the electrons) accelerates the local electrons to an equivalent energy, ionizing the incoming neutral atoms that have an electron-impact ionization threshold, eφ I , that is less than 1 2 m gas v 2 0 (MacLachlan et al 2009(MacLachlan et al , 2013. Note that it is only the relative speed between the magnetized plasma and gas that is important; a moving magnetized plasma can encounter a stationary neutral component: the critical requirement is that the plasma is localized by the ambient magnetic field.…”
Section: Alfvén Ionizationmentioning
confidence: 99%
“…In the model atmosphere results considered here, excitation to metastable states would need to occur via an alternative process such as gas discharges; cosmic-ray interactions; or even as part of the Alfvén ionization mechanism where bombardment from neutral flow drives the excitation. For example, simulations of electron avalanches (the precursor to a full gas discharge) in 1 mm gap of atmospheric Nitrogen have shown that the metastable density can reach ≈ 10 12 cm −3 (MacLachlan et al 2013). Furthermore, if in a localized volume of a BD, [M/H]= 0.0 model atmosphere (for example at an atmospheric pressure of ≈ 10 −10 bar), Alfvén ionization excited all the Helium from its ground state to its first metastable state, the metastable density would be ≈ 10 10 cm −3 (see Fig.…”
Section: Metastable States Of Gas-phase Speciesmentioning
confidence: 99%
“…A major challenge is to model cloud formation and its consequent effect on the surrounding environment, involving plasma processes such as non-spherical dust growth (Stark et al 2006) and electrical discharge events (MacLachlan et al 2013). Opik (1956) investigated the electrostatic disruption (or Coulomb explosion) of dust grains, where the electrostatic stress of a body holding a net charge exceeds its mechanical tensile strength (the maximum stress or pressure that a material can withstand while being pulled), resulting in it fracturing.…”
Section: Introductionmentioning
confidence: 99%